Prevalence of impostor syndrome in medical and non-medical students at the university of Faisalabad - Elahi, Ayesha; Sohail, Muneeba; Safdar, Maryam (Journal of the Pakistan Medical Association, 2026)
The study aimed to investigate the prevalence of imposter syndrome along with its relationship with self-esteem among medical and non-medical female university students. A cross-sectional study was conducted after informed consent from the 100 participants recruited with convenient sampling method from The University of Faisalabad. Data was collected through a self-administered questionnaire; Clance Imposter Phenomenon Scale (CIPS) to evaluate impostorism and the Rosenberg Self-esteem Scale (RSES) to evaluate self-esteem were used. The collected data was entered and analysed by IBM SPSS Version 23. The prevalence of impostor syndrome in medical students and non-medical students was 25(47.17%) and 19(40.43%) respectively. Whereas, the prevalence of low self-esteem in medical and non-medical was 14(26.42%) and 17(36.17%), respectively. This study revealed that there is no significant relationship between impostor syndrome and self-esteem with (3) with p=0.994. Key words: Impostor syndrome, Medical students, Non-medical students.